Constructivist Teaching Pedagogy: A Strategy for Innovation, Industrialization and Sustainable Development - Mbise, Stephano; Lekule, Chrispina (International Journal For Research In Educational Studies, 2020)
Knowledge and skills for socio-economic transformations are developed from learners' experience and interests rather than treating them as empty vessels to be filled with knowledge. All learning is filtered through pre-existing strategies. Hence, learning is more effective when learners are actively engaged. Based on this stand point, in this paper, we discuss the practice of constructivist pedagogy as a strategy for cultivating innovative minds and promoting skills that are needed for the realization of industrialization and sustainable development. In this paper, we highlight some factors hindering the practice of constructivist teaching pedagogy and suggest strategies that schools could adopt to encourage the practice constructivist teaching pedagogy. We also discuss the contribution of constructivist pedagogy in equipping learners with workable knowledge and skills. Based on our analysis of various empirical studies, we conclude with suggestions on how to practice constructivists teaching pedagogy as an indispensable approach to cultivate and promote innovative minds among learners. Throughout this paper, we underline and recommend pedagogical shift and adoption of new pedagogies that encourage and promote independent and critical thinking. In our view, this is the best approach through which learners can eventually become innovative producers of relevant knowledge which is required for industrialization and sustainable development.